2007
DOI: 10.1242/jcs.03390
|View full text |Cite
|
Sign up to set email alerts
|

LAP2α-binding protein LINT-25 is a novel chromatin-associated protein involved in cell cycle exit

Abstract: Lamina-associated polypeptide 2α (LAP2α) is a nuclear protein dynamically associating with chromatin during the cell cycle. In addition, LAP2α interacts with A-type lamins and retinoblastoma protein and regulates cell cycle progression via the E2F-Rb pathway. Using yeast two-hybrid analysis and three independent in vitro binding assays we identified a new LAP2α interaction partner of hitherto unknown functions, which we termed LINT-25. LINT-25 protein levels were upregulated during G1 phase in proliferating ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…In these cells, we confirmed that LAP2α was progressively down-regulated upon GFP-progerin expression. Since previous studies have revealed that LAP2α is down-regulated in noncycling wildtype cells, including quiescent, senescent, or differentiated cells (Markiewicz et al 2002(Markiewicz et al , 2005Naetar et al 2007), the observed down-regulation of LAP2α in progerin-expressing cells may be a consequence of progerinmediated cell cycle exit. However, LAP2α mRNA downregulation in these cells occurred already at a time point when the cells had no detectable proliferation defects.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In these cells, we confirmed that LAP2α was progressively down-regulated upon GFP-progerin expression. Since previous studies have revealed that LAP2α is down-regulated in noncycling wildtype cells, including quiescent, senescent, or differentiated cells (Markiewicz et al 2002(Markiewicz et al , 2005Naetar et al 2007), the observed down-regulation of LAP2α in progerin-expressing cells may be a consequence of progerinmediated cell cycle exit. However, LAP2α mRNA downregulation in these cells occurred already at a time point when the cells had no detectable proliferation defects.…”
Section: Discussionmentioning
confidence: 91%
“…Transient (quiescence) or stable (terminal differentiation and senescence) cell cycle exit has also been found to correlate with down-regulation of LAP2α expression and loss of nucleoplasmic lamins (Markiewicz et al 2002(Markiewicz et al , 2005Naetar et al 2007Naetar et al , 2008. We therefore tested whether the observed loss of LAP2α and nucleoplasmic lamins in HGPS cells correlated with progerin-induced proliferation defects.…”
Section: Loss Of Lap2α Precedes Progerin-dependent Proliferation Defementioning
confidence: 99%
“…These results indicated that terminal differentiation is accompanied by a reorganization of pericentric heterochromatin. It has also been demonstrated that distribution of heterochromatin is dependent of the state of cell proliferation-diffuse nuclear staining of HP1α was characteristic for non-dividing cells (Grigoryev et al 2004;Naetar et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In proliferating cells, LAP2a is essential and sufficient to target and retain a subset of lamins within the nuclear interior (Naetar et al 2007;Naetar et al 2008). Nucleoplasmic lamins are stable, but more mobile than peripheral lamins, suggesting interior lamins assemble differently or bind to chromatin (Moir et al 2000b).…”
Section: Regulation Of Signaling and Proliferation Control By Lamin-bmentioning
confidence: 99%